A Brief Discussion on Energy Considerations for GaAs Parabolic Quantum Dots - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
The hamiltonian operator corresponding to a GaAs parabolic quantum dot is formulated by analyzing carefully the terms of this operator. In this formulation, certain plasma aspects are discussed with respect to the hamiltonian. Our study is referred to the absence of electric and magnetic fields.